Modern and Contemporary Art Museum in Bandung: A Contextual Architecture Approach - Arief Perdana Putra; Venia Setyarandini; Nur Kharismawati Utami; Christanti Nugraheni (UJoST- Universal Journal of Science and Technology, 2023)
Bandung's rapidly growing creative industry has not been supported by a modern and contemporary art museum capable of accommodating exhibition, education, research, and community interaction within an integrated cultural facility. Existing museums primarily focus on historical collections and therefore have limited capacity to support contemporary artistic activities. Previous studies on museum architecture in Indonesia have generally emphasized formal exploration rather than developing a conceptual framework linking contextual analysis to architectural decision-making. This research aims to develop a design concept for a Modern and Contemporary Art Museum in Bandung using a contextual architectural approach through the Research by Design method. The research consisted of literature review, site observation, precedent studies, contextual analysis, user analysis, spatial programming, design synthesis, and conceptual evaluation. The findings reveal that contextual factors significantly influence building massing, spatial organization, environmental strategies, and the integration of public spaces. The study proposes the Contextual Creative Museum (CCM) Model, consisting of Context, Culture, Climate, Community, and Creative Space, as a conceptual framework for designing museums and other cultural facilities in urban environments.